Evolutionary origin of phytochrome responses and signaling in land plants. (1st March 2017) - Inoue, Keisuke; Nishihama, Ryuichi; Kohchi, Takayuki
Abstract: Phytochromes comprise one of the major photoreceptor families in plants, and they regulate many aspects of plant growth and development throughout the plant life cycle. A canonical land plant phytochrome originated in the common ancestor of streptophytes. Phytochromes have diversified in seed plants and some basal land plants because of lineage‐specific gene duplications that occurred during the course of land plant evolution. Molecular genetic analyses using Arabidopsis thaliana suggested that there are two types of phytochromes in angiosperms, light‐labile type I and light‐stable type II, which have different signaling mechanisms and which regulate distinct responses. In basal land plants, little is known about molecular mechanisms of phytochrome signaling, although red light/far‐red photoreversible physiological responses and the distribution of phytochrome genes are relatively well documented. Recent advances in molecular genetics using the moss Physcomitrella patens and the liverwort Marchantia polymorpha revealed that basal land plants show far‐red‐induced responses and that the establishment of phytochrome‐mediated transcriptional regulation dates back to at least the common ancestor of land plants. In this review, we summarize our knowledge concerning functions of land plant phytochromes, especially in basal land plants, and discuss subfunctionalization/neofunctionalization of phytochrome signaling during the course of land plant evolution. Abstract : Phytochrome photoreceptors that regulate many aspects of growth and development throughout the plant life cycle originated in the common ancestor of streptophytes and diversified during the course of land plant evolution. Recent advances in molecular genetics using the moss Physcomitrella patens and the liverwort Marchantia polymorpha revealed that basal land plants show FR‐induced responses and that the establishment of phytochrome‐mediated transcriptional regulation dates back to at least the common ancestor of land plants. In this review, we summarize our knowledge concerning functions of land plant phytochromes, especially in basal land plants, and discuss subfunctionalization/neofunctionalization of phytochrome genes in the lineages of land plants.